Gaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru SD Negeri 009 Penajam - Aji Luqman Panji; Ahmad Muadin; Sudadi Sudadi; Salehudin Salehudin (Journal on Education, 2023)
The leadership style of the principal plays a significant role in enhancing the performance of teachers under their supervision. This qualitative research, utilizing a descriptive method, aims to collect data on: (1) the principal's leadership style in improving work discipline, (2) the principal's leadership style in enhancing teachers' work motivation, (3) the principal's leadership style in promoting responsibility, and (4) the obstacles faced by the principal in enhancing teacher performance. Data were gathered through interviews, observations, and documentary studies.The findings indicate that the principal applies an instructive leadership style (telling) to improve discipline, a consultative leadership style (selling) to boost teachers' work motivation, and a delegative leadership style (delegating) to enhance teachers' responsibility. However, challenges such as declining teacher discipline, insufficient performance motivation, and a lack of teacher responsibility in learning were identified as obstacles faced by the principal.